Roller laser glazing process

Through the roll laser glazing process, the amorphous glazing layer is formed on the surface of the roll surface, which solves the problems of rapid wear and stress cracks of the roll wear-resistant layer, significantly improves the wear resistance and fatigue resistance of the roll, extends the service life and reduces the Production cost.

CN119194447APending Publication Date: 2024-12-27SINOSTEEL XINGTAI MACHINERY & MILL ROLL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411346080.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing rolls wear fast during steel rolling, resulting in a short service life of the roll and other strengthening processes prone to stress cracks.

Method used

Using the roll laser glaze technology, a laser glaze corrosion agent containing tungsten carbide and titanium carbide is sprayed, and the surface of the roll is scanned with a high-energy laser beam, so that it instantly exceeds the preset temperature and cools rapidly, forming a layer of about 15μm thick Amorphous glazed layer enhances the wear resistance and fatigue resistance of the roll.

Benefits of technology

It significantly improves the wear resistance and fatigue resistance of the roll, extends the roll life, avoids the occurrence of stress cracks, and significantly improves the corrosion resistance. The roll life is increased by more than 2 times, saving roll number and reducing production costs. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194447A_ABST
    Figure CN119194447A_ABST
Patent Text Reader

Abstract

The invention discloses a roller laser glazing process, which belongs to the technical field of laser processing, and comprises the following steps: step 1, normally grinding the surface of a roller, removing various attachments, and keeping the surface of the whole roller clean and consistent; step 2, uniformly spraying a laser glazing corrosive agent containing tungsten carbide and titanium carbide on the surface of the roller subjected to surface treatment, so that the surface of the roller is slightly oxidized and corroded, and meanwhile, tungsten carbide and titanium carbide super wear-resistant particles are attached to the surface; and 3, scanning the surface of the roller sprayed with the laser glazing corrosive agent containing tungsten carbide and titanium carbide by adopting a high-energy laser beam, so that the surface of the roller instantly exceeds a preset temperature and is rapidly cooled, and an amorphous glazing layer is formed on the surface of the roller. A layer of amorphous structure containing a super wear-resistant phase is formed on the surface of the roller through the laser glazing technology and the alloy permeation technology, the wear resistance is improved by more than one time, meanwhile, the stress crack problem of other strengthening technologies is solved, and safety and reliability are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of laser processing, in particular to a roller laser glazing process. Background Art

[0002] The roller is a cylindrical consumable part on the rolling mill that causes the rolled material to undergo plastic deformation and thus change its shape. The wear-resistant layer of the roller will be worn away during the steel rolling process. When the wear-resistant layer of the roller is consumed, the service life of the roller will end.

[0003] The service life of the roller mainly depends on the thickness and wear resistance of the wear-resistant layer. How to improve the wear resistance of the roller has always been a difficult problem for roller manufacturers. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a new type of roller laser glazing process. Through laser glazing technology and alloy penetration technology, a layer of amorphous structure containing super wear-resistant phase is formed on the surface of the roller, and the wear resistance is improved by more than 1 times. At the same time, the stress crack problem of other strengthening processes is overcome, and it is safe and reliable.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: A roller laser glazing process comprises the following steps: Step 1: Grind the roller surface normally to remove all kinds of attachments and keep the entire roller surface clean and consistent; Step 2, evenly spraying a laser glazing etchant containing tungsten carbide and titanium carbide on the surface of the roller after surface treatment, so that the surface of the roller is slightly oxidized and corroded, and super wear-resistant particles of tungsten carbide and titanium carbide are attached to the surface; Step 3, using a high-energy laser beam to scan the roller surface sprayed with a laser glazing etchant containing tungsten carbide and titanium carbide, so that the roller surface exceeds a preset temperature in an instant and cools rapidly, forming an amorphous glaze layer on the roller surface.

[0006] A further improvement of the technical solution of the present invention is that in step 2, the preparation method of the laser glazing etchant comprises: The hydrochloric acid ethanol solution and the hydrogen peroxide ethanol solution are mixed uniformly according to a volume ratio to obtain a mixed solution; Tungsten carbide and titanium carbide are mixed according to a mass ratio, and then mixed with a mixed liquid according to a mass fraction to obtain a laser glazing etchant.

[0007] A further improvement of the technical solution of the present invention is that the mass fractions of the hydrochloric acid ethanol solution and the hydrogen peroxide ethanol solution are both 10%.

[0008] A further improvement of the technical solution of the present invention is that the hydrochloric acid ethanol solution and the hydrogen peroxide ethanol solution are uniformly mixed in a volume ratio of 1:12.

[0009] A further improvement of the technical solution of the present invention is that tungsten carbide and titanium carbide are mixed in a mass ratio of 1:5.

[0010] A further improvement of the technical solution of the present invention is that tungsten carbide and titanium carbide are mixed according to a mass ratio and then mixed with the mixed liquid at a mass fraction of 8%.

[0011] A further improvement of the technical solution of the present invention is that in step 2, the thickness of the laser glazing etchant containing tungsten carbide and titanium carbide uniformly sprayed is 20 μm.

[0012] The further improvement of the technical solution of the present invention is that in step 3, the parameters of the high-energy laser beam are: the spot is a square spot of 0.3mm*0.3mm-1.0mm*1.0mm, and the laser density is 100-300W / cm 2 , scanning speed is 1000mm-5000mm / s, and laser power is 1000-1500W.

[0013] A further improvement of the technical solution of the present invention is that in step 3, the preset temperature is 1600°C.

[0014] A further improvement of the technical solution of the present invention is that in step 3, the thickness of the amorphous glaze layer is 15 μm.

[0015] Due to the adoption of the above technical solution, the technical progress achieved by the present invention is: 1. The present invention prepares an amorphous glaze layer with a thickness of about 15 μm on the surface of the roller. The glaze layer homogenizes structural components such as supersaturated solid solution and non-equilibrium phase alloy, improves corrosion resistance by dozens of times, eliminates micro defects on the surface of the roller, improves fatigue resistance and wear resistance of the roller, and constructs a surface friction and wear mechanism different from that used by conventional rollers.

[0016] 2. The amorphous glaze layer prepared by the present invention has tungsten carbide and titanium carbide super wear-resistant particles uniformly dispersed inside, which significantly improves the wear resistance of the roller and increases the roller life by more than 2 times.

[0017] 3. The fatigue resistance of the roller treated by the present invention is significantly improved, and the fatigue crack generation time is extended by more than 1 times; the corrosion resistance of the roller is significantly improved, avoiding the loss of the wear-resistant layer caused by corrosion and oxidation during use.

[0018] 4. In the present invention, the surface of the roller is rapidly melted and then rapidly cooled, the heat-affected zone is only tens of μm, the thermal stress and the structural stress are extremely small, and the generation of stress cracks is avoided.

[0019] 5. The laser beam in the present invention adopts a square spot, and the laser density at the edge of the spot and the overlapping area is uniform, which ensures that the strengthening effect of the entire amorphous glaze layer is uniform and consistent, avoiding the problems of uneven glazing effect and uneven stress distribution. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work. Figure 1 The present invention provides a process flow chart of roller laser glazing in an embodiment of the present invention. DETAILED DESCRIPTION

[0021] It should be noted that the terms "including" and "having" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or apparatus.

[0022] The present invention is further described in detail below with reference to the accompanying drawings and embodiments: like Figure 1 As shown, a roller laser glazing process includes the following steps: Step 1: Grind the roller surface normally to remove all kinds of attachments and keep the entire roller surface clean and consistent; Step 2, then evenly spraying a laser glazing etchant containing tungsten carbide and titanium carbide with a thickness of 20 μm, so that the surface of the roller is slightly oxidized and corroded, and super wear-resistant particles of tungsten carbide and titanium carbide are attached to the surface; Preparation of laser glazing etchant: 10% hydrochloric acid ethanol and 10% hydrogen peroxide ethanol solution are mixed at a mass fraction of 1:12 to obtain a mixed solution; tungsten carbide and titanium carbide are mixed at a mass fraction of 1:5, and then mixed with the mixed solution at a mass fraction of 8%.

[0023] Step 3, use a high-energy laser beam to scan the roller surface sprayed with a laser glazing etchant containing tungsten carbide and titanium carbide, so that the roller surface exceeds 1600°C in an instant and cools rapidly, forming an amorphous glaze layer with a thickness of about 15μm on the roller surface; during the melting process of the roller surface, super wear-resistant particles of tungsten carbide and titanium carbide simultaneously penetrate into the amorphous glaze layer.

[0024] Parameters of high energy laser beam: spot size is 0.3mm*0.3mm-1.0mm*1.0mm square spot, laser density is 100-300W / cm 2, scanning speed 1000mm-5000mm / s, laser power 1000-1500W.

[0025] Example 1 The millimeter rolling capacity of the original rollers of a certain rolling line is 3000 tons, and the roller laser glazing process provided by the present invention is used to process the rollers of the rolling line.

[0026] Step 1: Grind the roller surface normally to remove all kinds of attachments and keep the entire roller surface clean and consistent; Step 2, then evenly spraying a laser glazing etchant containing tungsten carbide and titanium carbide with a thickness of 20 μm, so that the surface of the roller is slightly oxidized and corroded, and super wear-resistant particles of tungsten carbide and titanium carbide are attached to the surface; Preparation of laser glazing etchant: 10% hydrochloric acid ethanol and 10% hydrogen peroxide ethanol solution are mixed at a mass fraction of 1:12 to obtain a mixed solution; tungsten carbide and titanium carbide are mixed at a mass fraction of 1:5, and then mixed with the mixed solution at a mass fraction of 8%.

[0027] Step 3, use a high-energy laser beam to scan the roller surface sprayed with a laser glazing etchant containing tungsten carbide and titanium carbide, so that the roller surface exceeds 1600°C in an instant and cools rapidly, forming an amorphous glaze layer with a thickness of about 15μm on the roller surface; during the melting process of the roller surface, super wear-resistant particles of tungsten carbide and titanium carbide simultaneously penetrate into the amorphous glaze layer.

[0028] Parameters of high energy laser beam: spot size is 0.3mm*0.3mm square spot, laser density is 100W / cm 2 , scanning speed 1000mm / s, laser power 1000W.

[0029] After laser glazing, the millimeter rolling capacity of the rollers increased to 7,500 tons, and the service life of the rollers increased to 2.5 times. The rolling line saved 35 rollers that year and the production cost was greatly reduced.

[0030] Example 2 The millimeter rolling capacity of the original rollers of a certain rolling line is 4000 tons, and the roller laser glazing process provided by the present invention is used to process the rollers of the rolling line.

[0031] Step 1: Grind the roller surface normally to remove all kinds of attachments and keep the entire roller surface clean and consistent; Step 2, then evenly spraying a laser glazing etchant containing tungsten carbide and titanium carbide with a thickness of 20 μm, so that the surface of the roller is slightly oxidized and corroded, and super wear-resistant particles of tungsten carbide and titanium carbide are attached to the surface; Preparation of laser glazing etchant: 10% hydrochloric acid ethanol and 10% hydrogen peroxide ethanol solution are mixed at a mass fraction of 1:12 to obtain a mixed solution; tungsten carbide and titanium carbide are mixed at a mass fraction of 1:5, and then mixed with the mixed solution at a mass fraction of 8%.

[0032] Step 3, use a high-energy laser beam to scan the roller surface sprayed with a laser glazing etchant containing tungsten carbide and titanium carbide, so that the roller surface exceeds 1600°C in an instant and cools rapidly, forming an amorphous glaze layer with a thickness of about 15μm on the roller surface; during the melting process of the roller surface, super wear-resistant particles of tungsten carbide and titanium carbide simultaneously penetrate into the amorphous glaze layer.

[0033] Parameters of high energy laser beam: spot size is 0.5mm*0.5mm square spot, laser density is 200W / cm 2 , scanning speed 2000mm / s, laser power 1200W.

[0034] After laser glazing, the millimeter rolling capacity of the rollers increased to 8,000 tons, and the service life of the rollers increased to 2 times. The rolling line saved 27 rollers that year and the production cost was greatly reduced.

[0035] Example 3 The millimeter rolling capacity of the original rollers of a certain rolling line is 2500 tons, and the roller laser glazing process provided by the present invention is used to process the rollers of the rolling line.

[0036] Step 1: Grind the roller surface normally to remove all kinds of attachments and keep the entire roller surface clean and consistent; Step 2, then evenly spraying a laser glazing etchant containing tungsten carbide and titanium carbide with a thickness of 20 μm, so that the surface of the roller is slightly oxidized and corroded, and super wear-resistant particles of tungsten carbide and titanium carbide are attached to the surface; Preparation of laser glazing etchant: 10% hydrochloric acid ethanol and 10% hydrogen peroxide ethanol solution are mixed at a mass fraction of 1:12 to obtain a mixed solution; tungsten carbide and titanium carbide are mixed at a mass fraction of 1:5, and then mixed with the mixed solution at a mass fraction of 8%.

[0037] Step 3, use a high-energy laser beam to scan the roller surface sprayed with a laser glazing etchant containing tungsten carbide and titanium carbide, so that the roller surface exceeds 1600°C in an instant and cools rapidly, forming an amorphous glaze layer with a thickness of about 15μm on the roller surface; during the melting process of the roller surface, super wear-resistant particles of tungsten carbide and titanium carbide simultaneously penetrate into the amorphous glaze layer.

[0038] Parameters of high energy laser beam: spot size is 1.0mm*1.0mm square spot, laser density is 300W / cm 2 , scanning speed 5000mm / s, laser power 1500W.

[0039] After laser glazing, the millimeter rolling capacity of the rollers increased to 6,000 tons, and the service life of the rollers increased to 2.4 times. The rolling line saved 31 rollers that year and the production cost was greatly reduced.

[0040] In addition, the upper and lower limits and interval values ​​of the process parameters (such as light spot, laser density, scanning speed, laser power, etc.) of the present invention can all realize the present invention, and the embodiments are not listed one by one here.

[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A roller laser glazing process, characterized in that: The following steps are involved: Step 1: Grind the roller surface normally to remove all kinds of attachments and keep the entire roller surface clean and consistent; Step 2, evenly spraying a laser glazing etchant containing tungsten carbide and titanium carbide on the surface of the roller after surface treatment, so that the surface of the roller is slightly oxidized and corroded, and super wear-resistant particles of tungsten carbide and titanium carbide are attached to the surface; Step 3, using a high-energy laser beam to scan the roller surface sprayed with a laser glazing etchant containing tungsten carbide and titanium carbide, so that the roller surface exceeds a preset temperature in an instant and cools rapidly, forming an amorphous glaze layer on the roller surface.

2. The roller laser glazing process according to claim 1, characterized in that: In step 2, the preparation method of the laser glazing etchant includes: The hydrochloric acid ethanol solution and the hydrogen peroxide ethanol solution are mixed uniformly according to a volume ratio to obtain a mixed solution; Tungsten carbide and titanium carbide are mixed according to a mass ratio, and then mixed with a mixed liquid according to a mass fraction to obtain a laser glazing etchant.

3. The roller laser glazing process according to claim 2 is characterized in that: The mass fractions of the hydrochloric acid ethanol solution and the hydrogen peroxide ethanol solution are both 10%.

4. The roller laser glazing process according to claim 2 is characterized in that: The hydrochloric acid ethanol solution and the hydrogen peroxide ethanol solution were uniformly mixed in a volume ratio of 1:

12.

5. The roller laser glazing process according to claim 2 is characterized in that: Tungsten carbide and titanium carbide are mixed in a mass ratio of 1:

5.

6. The roller laser glazing process according to claim 2, characterized in that: Tungsten carbide and titanium carbide are mixed according to a mass ratio and then mixed with the mixed liquid at a mass fraction of 8%.

7. The roller laser glazing process according to claim 1 is characterized in that: In step 2, a laser glazing etchant containing tungsten carbide and titanium carbide is uniformly sprayed to a thickness of 20 μm.

8. The roller laser glazing process according to claim 1 is characterized in that: In step 3, the parameters of the high-energy laser beam are: the spot is a 0.3mm*0.3mm-1.0mm*1.0mm square spot, and the laser density is 100-300W / cm 2 , scanning speed is 1000mm-5000mm / s, and laser power is 1000-1500W.

9. The roller laser glazing process according to claim 1, characterized in that: In step 3, the preset temperature is 1600°C.

10. The roller laser glazing process according to claim 1, characterized in that: In step 3, the thickness of the amorphous glaze layer is 15 μm.